Media Exposure and Acquisition Premium Evidence from Chinese Investing Companies - Shao, Ruchen; Wang, Yanting; Wang, Hao; Geng, Zongze; Ma, Li (Archives of Business Research, 2021)
Acquisition deals often draw the attention of the media and the media exposure influences the decisions of stakeholders. Especially attractive in recent years are deals that Chinese companies are investing actively both within China and across the globe. How does media exposure influence the price premium of the target companies that Chinese companies acquire? Building upon the literature of economics and psychology, we develop competing hypotheses on the potential effect. In addition, we argue that the effects of media exposure are different between the Chinese companies’ domestic and international acquisition deals. The data from the recent decade’s transactions indicate that media exposure is associated with the higher premium, supporting the attention-based view. In addition, we hypothesize the effect of media exposure is larger for international deals than for domestic deals. Theoretical and practical implications are discussed.